Effects of dietary forage to concentrate ratio on nutrient digestibility, ruminal fermentation and rumen bacterial composition in Angus cows - Hao Chen (Nature Portfolio, 2021)
Abstract This study evaluated effects of dietary forage to concentrate ratio (F:C) on the body weight, digestibility, ruminal fermentation and rumen bacterial composition in Angus cows. Three diets with different F:C (LCD: 65:35, MCD:50:50, and HCD: 35:65) were fed to ninety Angus cows (3.2 ± 0.18 years old, 387.2 ± 22.6 kg). The average daily gain (ADG) and ammonia nitrogen concentration increased (P = 0.039 and P = 0.026, respectively), whereas the acetate to propionate ratio (P = 0.027) and the neutral detergent fiber (NDF) digestibility decreased with increasing concentrate level. The acetate concentration and ruminal pH (P = 0.033 and P = 0.029, respectively) decreased by feeding HCD diet. Serum amyloid A (SAA), C-reactive protein (CRP), haptoglobin (Hp) and lipopolysaccharide binding protein (LBP) increased under the HCD. The relative abundances of Bacteroidetes, Fibrobacterota, Prevotella and Prevotellaceae UCG-003 decreased, whereas the relative abundances of Ruminococcaceae NK4A214 group, Saccharofermentans and Spirochaetota increased with increasing dietary concentrate level. Our study provides a better understanding of rumen fermentation parameters and microbiota under a wide range of dietary F:C ratios, supporting the potential dietary manipulation of microbes, which could enhance feed digestibility associated with cow rearing.